Lithium-ion rechargeable battery
Patent Information
- Application Number
- JP2025062469
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-04
- Publication Date
- 2026-10-16
AI Technical Summary
【0016】 本発明によれば、レート特性を維持しつつ、安全性を向上させることができる。
Smart Images

Figure 2026168913000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to a lithium-ion secondary battery. [Background technology]
[0002] Lithium-ion rechargeable batteries offer advantages such as miniaturization, weight reduction, and high capacity due to their high energy density. For example, batteries using high-energy-density active materials such as NCM (Nickel-Cobalt-Manganese Composition) or layered compounds like lithium cobalt oxide (LCO) as the positive electrode are widely used in applications ranging from small devices like wearable devices and power tools to large-scale applications in automobiles and industrial use. In particular, for large-scale applications, the use of lithium-ion rechargeable batteries is increasing, and in recent years, demand for applications used near people, such as in automobiles, has been growing, making safety a crucial factor.
[0003] Regarding battery safety, overcharging and external short circuits can be improved through system and module design. On the other hand, internal short circuits within cells cannot be prevented by module design alone, and countermeasures are required on the cell side. As a test for this countermeasure, the nail-piercing test, which simulates an internal short circuit, is known. In this test, a nail is driven into the battery at a constant speed to forcibly short-circuit the positive and negative terminals of the battery, and the battery's resistance to internal short circuits can be confirmed.
[0004] In lithium-ion secondary batteries, highly flammable organic solvents are used as the electrolyte. When thermally unstable layered compounds such as NCM are used as the positive electrode active material, there is a risk of ignition in the event of internal short circuits caused by, for example, punctures by metal fragments from the outside or nail penetration. Therefore, improvements in safety are required.
[0005] On the other hand, in conventional lithium-ion secondary battery configurations, increasing the electrode resistance to improve safety during internal short circuits caused by nails often sacrificed rate characteristics. Conversely, improving rate characteristics tended to worsen safety during internal short circuits caused by nails, making it a challenge to achieve both performance levels simultaneously.
[0006] Patent Document 1 aims to suppress the separation of the separator and electrode during cycling and to improve the heat resistance of the separator. It provides an inorganic particle layer on at least one surface of the porous membrane of the separator, in which inorganic particles account for 80% or more of the total volume of the layer, and a porous resin layer integrated with the inorganic particle layer on the surface of the inorganic particle layer. [Prior art documents] [Patent Documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2020-64879 [Overview of the Initiative] [Problems that the invention aims to solve]
[0008] However, Patent Document 1 does not mention rate characteristics, and the separator described in Patent Document 1 may have adverse effects on rate characteristics because the porous resin layer integrated with the inorganic particle layer inhibits lithium ion movement.
[0009] This invention has been made in view of the above circumstances, and aims to provide a lithium-ion secondary battery that can improve safety while maintaining rate characteristics. [Means for solving the problem]
[0010] To address the above challenges, we conducted extensive research and discovered that by using carbon nanotubes as a conductive additive for the positive electrode, satisfying certain conditions when mixed with the positive electrode active material, and combining them with a separator having an inorganic coating layer, we could improve safety during nail penetration while maintaining rate characteristics. This led to the completion of the present invention.
[0011] The lithium-ion secondary battery according to the present invention comprises a positive electrode, a negative electrode, and a separator. The positive electrode is composed of a positive electrode composite layer comprising a positive electrode active material, a conductive additive, and a binder, and a current collector foil. The positive electrode active material comprises a first positive electrode active material and a second positive electrode active material. The first positive electrode active material is a layered compound represented by the general formula shown in (1) below, and the second positive electrode active material is a phosphorylated compound having an olivine structure represented by the general formula shown in (2) below. The conductive additive contains carbon nanotubes in a proportion greater than 0.4% by weight and less than 1.0% by weight relative to the total weight of the positive electrode composite layer. The separator has a coating layer of an inorganic material on at least one surface of a sheet that serves as the substrate for the separator. When the larger of the tensile strengths in the TD direction and MD direction of the substrate is A and the smaller of the tensile strengths is B, the A / B value is 1.0 or more and 5.0 or less. Li a Ni x Co y M1 1-x-y O2 (however, 0 <a≦1.2、0≦x≦0.9、0<y≦1、0<x+y≦1)···(1) LiMn z M2 b Fe 1-z-b PO4 (however, 0 <z≦0.9、0≦b≦0.1、0<z+b<1)···(2) M1 is commonly one or more elements selected from Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Ti, Cr, Pb, Sb, and B, and M2 is commonly one or more elements selected from Na, Mg, Sc, Y, Co, Ni, Cu, Zn, Al, Ti, Cr, Pb, Sb, and B.
[0012] Further, in the lithium ion secondary battery according to the present invention, in the above invention, it is more preferable that the inorganic material is any one of alumina, barium sulfate, and boehmite.
[0013] Further, in the lithium ion secondary battery according to the present invention, in the above invention, it is more preferable that the total thickness of the coating layer is 2 μm or more.
[0014] Further, in the lithium ion secondary battery according to the present invention, in the above invention, it is more preferable that the coating layer is coated on both surfaces of the base material.
[0015] Further, in the lithium ion secondary battery according to the present invention, in the above invention, it is more preferable that the average fiber diameter of the carbon nanotubes is 4 nm or more and 10 nm or less. Effects of the Invention
[0016] According to the present invention, safety can be improved while maintaining rate characteristics. Brief Description of the Drawings
[0017] [Figure 1] Figure 1 is a perspective view for explaining the configuration of a lithium ion secondary battery according to one embodiment of the present invention. [Figure 2] Figure 2 is a cross-sectional view taken along line A-A shown in Figure 1. Modes for Carrying Out the Invention
[0018] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following descriptions. In addition, various modifications or improvements can be added to the present embodiment, and forms with such modifications or improvements added can also be included in the present invention. Although Figures 1 and 2 show an example configuration of a stacked lithium-ion secondary battery as an example of an embodiment, the shape of the lithium-ion secondary battery in the present invention is not particularly limited and may be flat, cylindrical, prismatic, or coin-shaped. Furthermore, the casing of the lithium-ion secondary battery is not particularly limited and known materials such as laminate film, aluminum, aluminum alloy, and stainless steel can be used.
[0019] (Embodiment) Figure 1 is a perspective view illustrating the configuration of a lithium-ion secondary battery according to one embodiment of the present invention. Figure 2 is a cross-sectional view taken along line AA shown in Figure 1.
[0020] The lithium-ion secondary battery 1 is a stacked lithium-ion battery comprising an outer casing 2 formed in a bag shape by overlapping two laminate films so that the heat-sealable resin layers face each other and heat-sealing the outer edges.
[0021] The outer casing 2 is formed into a bag shape by overlapping two laminate films so that the heat-sealable resin layers face each other, and then heat-sealing the outer edges. The electrode group 3 and the non-aqueous electrolyte are housed inside the outer casing 2. The electrode group 3 is inserted through the opening of the outer casing 2, and the opening of the outer casing 2 is heat-sealed to enclose the electrode group 3 in an airtight manner.
[0022] As the laminate film, a composite film having a metal layer with a heat-sealable resin layer is preferably used. The metal layer is not particularly limited as long as it prevents moisture from entering from the outside while improving the overall strength of the sheet. For example, aluminum foil, stainless steel foil, etc., can be used as the metal layer. Furthermore, while the heat-sealable resin layer is not particularly limited, polyethylene and polypropylene are preferably used from the viewpoint of a heat-sealable temperature range and the ability to block non-aqueous electrolytes. Here, for protecting the metal layer, a protective layer may be provided on the surface opposite to the heat-fusible resin layer. The protective layer is also not particularly limited, but nylon, PET and the like are suitably used. Further, in order to improve the adhesion between the metal layer and the heat-fusible resin layer, an adhesive layer may be provided between the two.
[0023] As shown in Figure 2, the electrode group 3 has a structure in which a positive electrode 4, a negative electrode 5, and a separator 6 interposed between the positive electrode 4 and the negative electrode 5 are stacked as a set such that the negative electrode 5 is positioned at the outermost layer, and a plurality of the sets are stacked.
[0024] (Positive Electrode) The positive electrode 4 is composed of a positive electrode current collector 42, and positive electrode mixture layers 41 formed on both surfaces or one surface of the positive electrode current collector 42. The positive electrode 4 has a plate shape.
[0025] The positive electrode mixture layer 41 contains a positive electrode active material, a conductive agent, and a binder.
[0026] <Positive Electrode Active Material> The positive electrode active material includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material is a layered compound represented by the general formula shown in the following formula (1). Li a Ni x Co y M1 1-x-y O2 (where 0<a≦1.2, 0≦x≦0.9, 0<y≦1, 0<x+y≦1) ···(1) In the above formula (1), M1 is at least one selected from sodium (Na), magnesium (Mg), scandium (Sc), yttrium (Y), manganese (Mn), iron (Fe), copper (Cu), zinc (Zn), aluminum (Al), titanium (Ti), chromium (Cr), lead (Pb), antimony (Sb) and boron (B). In the following description, NCM is used as the positive electrode active material represented by the above formula (1).
[0027] Furthermore, for the purpose of improving cycle characteristics and thermal stability, the surface of the layered oxide may be coated with an inorganic substance such as magnesium oxide, aluminum oxide, aluminum fluoride, niobium oxide, titanium oxide, or tungsten oxide, or with an ion-conducting polymer such as polyethylene glycol, polyethylene oxide, their derivatives, or salts.
[0028] The second positive electrode active material is a phosphoric acid compound represented by the following formula (2). LiMn z M2 b Fe 1-z-b PO4 (however, 0 <z≦0.9、0≦b≦0.1、0<z+b<1) ···(2) In equation (2) above, M2 is at least one selected from Na, Mg, Sc, Y, cobalt (Co), nickel (Ni), Cu, Zn, Al, Ti, Cr, Pb, Sb, and B. In the following explanation, LMFP was used as the positive electrode active material represented by equation (2) above.
[0029] The phosphate compound represented by equation (2) above has an olivine structure and is a material with a charge / discharge potential close to that of layered rock salt type oxides and a high energy density. When the respective active materials are mixed, they exhibit a high energy density in the same upper and lower voltage range as when layered rock salt type oxides are used. Furthermore, the surface of the olivine compound may be coated with a carbon material to improve electrical conductivity. The weight ratio of the olivine-structured phosphorylated compound to the total weight of the positive electrode active material is preferably 60% by weight or less, and more preferably 25% by weight or less, from the viewpoint of energy density. In addition, the weight ratio is preferably 10% by weight or more, and more preferably 20% by weight or more, from the viewpoint of sufficiently reducing the amount of heat generated during thermal decomposition.
[0030] Whether or not NCM and LMFP are present in the positive electrode active material can be confirmed by observation using a scanning electron microscope (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray diffraction (XRD).
[0031] <Conductive agent> The conductive agent is not particularly limited, and known or commercially available ones can be used. Examples of conductive agents include carbon black such as acetylene black and Ketjen black, carbon nanotubes, carbon fibers, activated carbon, and conductive carbon such as graphite. The conductive agent can be used individually or as a mixture of several of these.
[0032] <Binding agent> The binder is not particularly limited, and known or commercially available binders can be used. Examples include fluororesins such as polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE), polyvinylpyrrolidone (PVP), polyvinyl chloride (PVC), polyethylene (PE), polypropylene (PP), ethylene-propylene copolymer, styrene-butadiene rubber (SBR), acrylic resin, polyvinyl alcohol (PVA), or carboxymethylcellulose (CMC). The binder can be used individually, or as a mixture or copolymer of two or more of these substances.
[0033] <Dispersant> Dispersants are not always necessary, but they can be added if you want to further disperse the conductive agent. Typical dispersants include polyvinylpyrrolidone (PVP), for example.
[0034] In lithium-ion secondary battery 1, it is desirable that the positive electrode composite layer 41 contains carbon nanotubes as a conductive agent in a proportion greater than 0.4% by weight but less than 1.0% by weight relative to the total weight of the positive electrode composite layer, and it is more preferable that it contains only carbon nanotubes as a conductive agent. If the amount of carbon nanotubes added is 0.4% by weight or less, the rate characteristics deteriorate significantly, and if the amount of carbon nanotubes added is 1.0% by weight or more, ignition is more likely to occur when a nail is driven into the battery. This is thought to be because the current value flowing from the electrode to the nail increases when a nail is driven into the battery.
[0035] The average fiber diameter of the carbon nanotubes is preferably between 4 nm and 10 nm. If the average fiber diameter of the carbon nanotubes is less than 4 nm, the carbon nanotubes tend to tangle and form clumps, making it easier for regions with localized low resistance to occur. Also, if the average fiber diameter of the carbon nanotubes is greater than 10 nm, the number of added carbon nanotubes per unit weight decreases, resulting in areas where conductive paths cannot be sufficiently formed, and thus the rate characteristics deteriorate.
[0036] The presence or absence of carbon nanotubes and their average fiber diameter can be confirmed by observing the electrode surface using a scanning electron microscope (SEM) and a transmission electron microscope (TEM). Fiber diameter can be determined by measuring the length in the short direction of the carbon nanotube fibers observed at a field of view of 20,000x or higher. The average fiber diameter of carbon nanotubes was calculated by obtaining the fiber diameters of 100 or more carbon nanotubes using the above method and taking the number average.
[0037] Furthermore, the fiber length of the carbon nanotubes is preferably between 5 μm and 2 mm. If the fiber length is less than 5 μm, it may not be possible to sufficiently form conductive paths between particles, which may lead to a decrease in rate characteristics. Also, if the fiber length is longer than 2 mm, aggregation is likely to occur when preparing the slurry, resulting in areas where conductive paths cannot be sufficiently formed, thus reducing the rate characteristics.
[0038] Although the detailed mechanism by which safety was improved while maintaining rate characteristics is not clear, the following phenomena are thought to be occurring in lithium-ion secondary batteries.
[0039] When carbon black, which is widely used in general lithium-ion secondary batteries, is used as a conductive agent, a thicker layer of conductive agent is formed around the active material particles compared to when carbon nanotubes are used. This layer is formed by the local aggregation of the conductive agent and is thought to be a layer with high electronic conductivity. When a foreign object such as a nail pierces the electrode and causes an internal short circuit, a large current is thought to flow locally from this aggregated area, generating a large amount of heat.
[0040] On the other hand, carbon nanotubes, compared to carbon black and the like, can adequately maintain their rate characteristics even when their usage is reduced, making them a conductive agent that easily exists as a thin layer between active material particles. This layer is expected to have fewer aggregated areas and fewer areas of localized low resistance compared to a layer made of carbon black. As a result, the current that flows when a nail is driven into the electrode will be smaller than when carbon black is used, and the amount of heat generated will also be less, thus reducing the area over which the active material undergoes thermal decomposition.
[0041] Furthermore, by using an olivine compound as part of the positive electrode active material, the amount of heat generated during the thermal decomposition of the positive electrode can be reduced, thereby keeping the decomposition heat of the active material to an appropriate level. This means that even if thermal decomposition of the positive electrode active material occurs in a very small area due to a short circuit caused by a foreign object such as a nail piercing the electrode, the surrounding active material can be prevented from undergoing thermal decomposition.
[0042] Based on the above, it is hypothesized that by adding an appropriate amount of carbon nanotubes and using an olivine compound as part of the positive electrode active material, the resistance distribution can be made uniform, and the amount of heat generated during thermal decomposition can be suppressed, thereby maintaining the rate characteristics while keeping the current and heat generated by the short circuit during internal short circuits to an appropriate level.
[0043] <Positive electrode current collector> The positive electrode current collector 42 is not particularly limited, and known or commercially available ones can be used. Examples of the positive electrode current collector 42 include rolled foil made of aluminum, aluminum alloy, copper, nickel, or stainless steel, and porous metals such as porous aluminum. Among these candidates for the positive electrode current collector, aluminum or aluminum alloy is preferred because it has high electrical conductivity, excellent corrosion resistance in the electrolyte, and is a lightweight metal.
[0044] The presence of an active material capable of intercalating and deintercalating lithium in the electrode's constituent materials can be confirmed by cyclic voltammetry. By preparing the target electrode as the working electrode, using lithium metal as the counter electrode, and constructing a coin cell with a separator in between, and performing several cycles of cyclic voltammetry measurements using an electrochemical test apparatus, it is possible to confirm whether lithium is capable of intercalating and deintercalating lithium by observing the reversible occurrence of redox reaction peaks.
[0045] [Electrode fabrication method] The positive electrode can be manufactured, for example, by the following method. First, the positive electrode active material, conductive agent, binder, and dispersant mentioned above are dispersed in a solvent to prepare a positive electrode slurry. A thickening agent may be further added to the positive electrode slurry. Subsequently, the positive electrode slurry is applied to one or both sides of the positive electrode current collector, dried to form a positive electrode composite layer, and then rolled to produce a plate-shaped positive electrode.
[0046] <Solvent> The solvent used in preparing the positive electrode slurry is not particularly limited, and known or commercially available solvents can be used. Examples of solvents include N-methyl-2-pyrrolidone (NMP), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), and water. When polyvinylidene fluoride (PVDF) is used as the binder, it is preferable to use N-methyl-2-pyrrolidone (NMP) as the solvent. When styrene-butadiene rubber (SBR), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), or carboxymethylcellulose (CMC) is used as the binder, it is preferable to use water as the solvent. Furthermore, it is preferable to use polyvinylpyrrolidone (PVP) as the dispersant.
[0047] Furthermore, the positive electrode 4 has a positive electrode lead 43 extending from the positive electrode composite layer 41 by the positive electrode current collector 42. The positive electrode lead 43 extends from the right side, for example, in Figure 2. Each positive electrode lead 43 is bundled at its tip within the outer casing 2 and joined to each other by ultrasonic welding, resistance welding, or the like. The positive electrode terminal 7 has one end joined to the joint of the positive electrode lead 43, and the other end extends to the outside through the sealing portion of the outer casing 2.
[0048] (Negative electrode) The negative electrode 5 consists of a negative electrode current collector 52 and a negative electrode composite material layer 51 formed on one or both sides of the negative electrode current collector 52. Here, the negative electrode composite material layer 51 of the outermost negative electrode 5 is formed on the surface of the negative electrode current collector 52 facing the separator 6. In contrast, the negative electrode composite material layer 51 of the negative electrodes 5 located between the positive electrodes 4, excluding the outermost negative electrode 5, is formed on both sides of the negative electrode current collector 52.
[0049] The negative electrode composite layer 51 contains a negative electrode active material, a conductive agent, and a binder. The negative electrode active material is not particularly limited as long as it is a substance capable of intercalating and releasing lithium. Examples of negative electrode active materials include pyrolysis carbons, pitch coke, needle coke, petroleum coke and other cokes, natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, glassy carbon, organic polymer compound sintered bodies (made by sintering and carbonizing phenolic resin, furan resin, etc.), carbon fibers, carbon black, activated carbon and other carbons, or metallic materials such as Al, Si, Sn, or alloy materials. As the negative electrode active material, cokes and carbons that have stable charge-discharge characteristics and readily form an SEI (Solid Electrolyte Interphase) film on their surface are preferred, with graphite such as natural graphite or artificial graphite being more preferred.
[0050] <Conductive agent> The conductive agent is not particularly limited, and known or commercially available ones can be used. For example, the same conductive agent used for the positive electrode described above can be used. Furthermore, a configuration without a conductive agent is also possible.
[0051] <Binding agent> The binder is not particularly limited, and known or commercially available binders can be used. Examples include fluororesins such as polyvinylidene fluoride (PVDF) and polytetrafluoroethylene (PTFE), fluororubber, styrene-butadiene rubber (SBR), carboxymethylcellulose (CMC), core-shell binder, polyvinyl alcohol, or polyimide resins such as polyimide and polyamide-imide. The binder can be used individually, or as a mixture or copolymer of two or more of these substances.
[0052] <Negative electrode current collector> The negative electrode current collector 52 is not particularly limited, and known or commercially available ones can be used. For example, the negative electrode current collector 52 can be made of rolled foil made of copper, copper alloy, aluminum or stainless steel, porous metal such as porous aluminum, etc. The negative electrode current collector is preferably made of copper or a copper alloy.
[0053] Furthermore, the negative electrode 5 has, for example, a negative electrode current collector 52 with a negative electrode lead 53 extending from the negative electrode composite layer 51. In Figure 2, for example, the negative electrode lead 53 extends from the left side. Each negative electrode lead 53 is bundled at its tip within the outer casing 2 and joined to one another. The negative electrode terminal 8 has one end joined to the joint of the negative electrode lead 53, and the other end extends to the outside through the sealing portion of the outer casing 2.
[0054] (Non-aqueous electrolyte) The non-aqueous electrolyte contains a non-aqueous solvent in which a lithium salt is dissolved. Examples of lithium salts include one or more mixtures selected from the group consisting of LiBF4, LiPF6, Li(FSO2)2N, Li(CF3SO2)2N, and LiPO2F2. The non-aqueous solvent is not particularly limited, but examples include one or more mixed solvents selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), methyl propionate, ethyl propionate, propyl propionate, methyl acetate, methyl formate, methyl butyrate, dioxolane, 2-methyltetrahydrofuran, tetrahydrofuran, dimethoxyethane, γ-butyrolactone, acetonitrile, and benzonitrile. DMC, DEC, DPC, EMC, EC, and PC are particularly preferred. In particular, it is preferable to include EC that enables good film formation on the negative electrode active material.
[0055] (Separator) The separator 6 is not particularly limited, and known or commercially available separators can be used. For example, the separator 6 can be a sheet made of a microporous membrane made of polyethylene resin, polyolefin resin such as polypropylene resin, polyimide resin, or polytetrafluoroethylene (PTFE) resin. The microporous membrane or nonwoven fabric may be a single layer or a multilayer structure. The separator 6 has a coating layer formed on one or both sides of the microporous membrane using an inorganic material to improve heat resistance and the ability to replenish the non-aqueous electrolyte.
[0056] The material of the coating layer on the separator 6, and whether or not a coating layer exists, can be confirmed by SEM-EDS and XRD. Furthermore, the thickness of the coating layer on the separator can be confirmed by SEM-EDS after the separator's cross-section has been prepared using a cross-section polisher or razor.
[0057] In this embodiment, as described above, the separator 6 has a coating layer made of an inorganic material on at least one side of the base sheet. The base sheet is formed using resin. From the viewpoint of ensuring safety against external short circuits and overcharging through the shutdown function, it is preferable to use polyethylene (PE) for this sheet. The separator 9 may be composed solely of PE, or it may have a layered structure in which PE is combined with polypropylene (PP), polyimide, aramid, etc., from the viewpoint of heat resistance and oxidation resistance. For example, a separator consisting of a three-layer structure of PP / PE / PP, in which PP is arranged on both sides of a base layer made of PE, may be used. The detailed mechanism by which separator 6 improves safety is not clear, but the following phenomena are thought to be occurring.
[0058] Here, carbon nanotubes tend to be thinly and uniformly distributed around the active material particles, resulting in a uniform resistance distribution. Therefore, by selecting carbon nanotubes as the conductive additive for positive electrode 4 and adding them in an amount sufficient to maintain rate characteristics, the area where resistance is locally low can be reduced. Furthermore, if an olivine compound is used as part of the positive electrode active material, the chain reaction of thermal decomposition caused by localized thermal decomposition of the active material can be suppressed. As a result, when a nail is driven into the electrode, the heat generated during a short circuit is kept to a moderate temperature. In this case, if a separator 6 coated with an inorganic material is used, although the short circuit area will melt due to the generated heat, the shrinkage of the separator will be minimal, preventing the short circuit from expanding and thus suppressing thermal runaway.
[0059] In contrast, even if carbon nanotubes are used within the range specified in this embodiment, if a separator without an inorganic material coating layer is used, the heat generated by the short circuit will cause the separator to shrink, expanding the short circuit area. This makes it impossible to suppress subsequent heat generation, which is likely to lead to thermal runaway.
[0060] Furthermore, even when using an inorganic material coated separator, if the electrode contains only the amount of carbon black (CB)-based conductive additive necessary to ensure the cell's rate characteristics, the acetylene black will be unevenly distributed in the gaps between particles, creating areas of low resistance locally. By passing through these areas, a large current will be generated locally. This results in a very large amount of heat being generated during a short circuit, and a large area of the coated separator is heated. Although the thermal shrinkage rate of the coated separator is small, the amount of shrinkage of the separator as a whole increases due to the wide heating area, making it impossible to prevent a short circuit and leading to thermal runaway.
[0061] In the separator 6, from the viewpoint of improving internal short-circuit resistance, the sheet that serves as the base material has a ratio of A / B of 1.0 to 5.0, where A is the larger of the tensile strengths in the TD direction and MD direction of the base material, and B is the smaller of the tensile strengths. Furthermore, it is more preferable that the A / B ratio of the sheet is between 1.0 and 3.0. Here, the MD direction is the direction in which the resin flows when forming the substrate, and the TD direction is the direction perpendicular to the direction in which the resin flows (MD direction).
[0062] In this case, if the A / B value is greater than 5.0, when a foreign object such as a nail is embedded, the separator will tear in a specific direction, but the positive and negative electrodes will have circular or cross-shaped cuts due to the shape of the foreign object, resulting in a large area where there is no separator between the positive and negative electrodes.
[0063] Furthermore, when the A / B value is between 1.0 and 5.0, the separator is less likely to tear in only one direction when a foreign object such as a nail penetrates it. This increases the probability of it tearing in the same shape as the positive and negative electrodes, making it more likely for the separator to get between the positive and negative electrodes, thus improving nail penetration resistance. When the A / B value is between 1.0 and 3.0, the separator becomes less likely to tear in a specific direction. This phenomenon reduces the number of short circuits inside the battery, thus improving its resistance to nail penetration. Furthermore, it is more preferable that the absolute value of B is 1 or greater. When the absolute value of B is 1 or greater, the separator is less likely to tear when foreign objects such as nails are embedded in it, and the separator itself is more likely to stretch due to friction with the foreign object, causing it to enter the space between the positive and negative electrodes, thus improving resistance to nail penetration.
[0064] Here, the inorganic material used to form the coating layer on the separator 6 is not particularly limited, and materials commonly used as separators for lithium-ion secondary batteries can be used. However, from the viewpoint of cost reduction, it is preferable to use alumina, barium sulfate, or boehmite. The thickness of the coating layer made of the inorganic material is preferably 1 μm or more. When the coating layer made of the inorganic material (inorganic coating layer) is within the above range, the shrinkage of the separator can be significantly suppressed, and the expansion of short circuits due to the shrinkage of the separator can be suppressed.
[0065] It is even more preferable that the inorganic coating layer is formed on both sides of the base sheet. By forming the inorganic coating layer on both sides of the base sheet, it is possible to prevent the separator 6 from bending in a specific direction when it shrinks due to heat, thereby more reliably suppressing the expansion of the short circuit.
[0066] The total thickness of the inorganic coating layer is preferably 2.0 μm or more, and more preferably 4.0 μm or more. When the total thickness of the inorganic coating layer is 2.0 μm or more, it is possible to significantly reduce the thermal shrinkage rate of the coating separator, and when it is 4.0 μm or more, it is possible to further reduce the thermal shrinkage rate of the coating separator at higher temperatures. Furthermore, from the viewpoint of improving the energy density of the battery, the inorganic coating layer is preferably 8.0 μm or less in thickness, and more preferably 6.0 μm or less.
[0067] The shape of the electrode elements is not particularly limited; the positive electrode, negative electrode, and separator may be wound together, stacked in a single-sheet configuration, or folded in a zigzag pattern.
[0068] It is preferable that such lithium-ion secondary batteries undergo pretreatment, such as initial charging and gas evacuation, before being used as batteries. For initial charging, for example, after injecting a non-aqueous electrolyte, constant current charging is performed at a small current value until the rated capacity reaches 10%. After such initial charging, gas generated inside the casing during the initial charging is evacuated. Gas evacuation is performed, for example, by placing the casing in a reduced pressure chamber with a part of the sealing portion open. Gas evacuation can be accelerated, for example, by pressing the casing from the outside during gas evacuation.
[0069] The capacity of the lithium-ion secondary battery 1 is preferably 50 Ah or less. When the capacity is 50 Ah or less, the short-circuit time that occurs within the electrode element when a nail is driven into it is shortened, making it possible to suppress ignition more reliably.
[0070] The presence of an active material capable of intercalating and deintercalating lithium in the electrode's constituent materials can be confirmed by cyclic voltammetry. By preparing the target electrode as the working electrode, using lithium metal as the counter electrode, and constructing a coin cell with separator 6 in between, and performing several cycles of cyclic voltammetry measurements using an electrochemical test apparatus, it is possible to confirm whether lithium is capable of intercalating and deintercalating lithium by observing the reversible occurrence of redox reaction peaks.
[0071] Furthermore, the capacity of the lithium-ion secondary battery 1 can be confirmed by charge-discharge testing. Using the upper and lower voltage limits specified by the manufacturer, charging is performed at 0.5 ItA, with CV switching at the upper voltage limit and a 0.05 ItA cutoff. Discharging is performed at 0.2 ItA, with a cutoff at the lower voltage limit. The battery capacity can then be confirmed from the discharge capacity.
[0072] The rate characteristics of lithium-ion secondary battery 1 can be confirmed by charge-discharge testing. Using the upper and lower voltage limits specified by the manufacturer, charging is performed at 0.5 ItA, with CV switching at the upper voltage limit and a 0.05 ItA cutoff. Discharging is performed at 0.2 ItA and 1 ItA, with a cutoff at the lower voltage limit. The discharge capacity at each discharge rate is obtained and confirmed by the ratio of the capacity at 1 ItA discharge to the capacity at 0.2 ItA discharge.
[0073] In the embodiment described above, the lithium-ion secondary battery 1 contains carbon nanotubes as a conductive additive in a proportion greater than 0.4% by weight and less than 1.0% by weight relative to the total weight of the positive electrode composite layer, and the separator 6 has a coating layer of an inorganic material on at least one surface of the sheet that serves as the substrate for the separator, and when the stronger tensile strength of the sheet that serves as the substrate for the separator 6 in the TD direction and the MD direction is denoted as A and the weaker tensile strength as B, the A / B value is set to be between 1.0 and 5.0, thereby improving safety while maintaining rate characteristics. [Examples]
[0074] The present invention will be described in more detail below with reference to examples, but the present invention is not limited in any way by the following examples.
[0075] (Example 1) <Fabrication of the positive electrode> LiNi 0.5 Co 0.2 Mn 0.3 O2 (commonly known as NCM523) 77.8% by weight, LiMn 0.7 Fe 0.3 A cathode active material slurry was prepared by mixing 19.5% by weight of PO4(LMFP), 0.7% by weight of carbon nanotubes (CNTs) with an average fiber diameter of 6 nm and a length of 10 μm as a conductive agent, 2.0% by weight of polyvinylidene fluoride (PVDF) as a binder, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) as a viscosity adjusting solvent.
[0076] The obtained slurry was applied to both sides of a 20 μm thick, non-perforated aluminum foil, which served as the current collector. After drying, it was pressed with a roll press to obtain electrodes. The amount of electrode composite applied to each side was 130 g / m². 2 The electrode density was adjusted to 3.1 g / cc. Subsequently, the portion was cut so that the uncoated portion protruded in a rectangular shape from one side of the rectangular area where the positive electrode composite layer was coated, forming the positive electrode current collector lead.
[0077] <Fabrication of the negative electrode> A negative electrode active material slurry was prepared by mixing 98.0% by weight of graphite as the negative electrode active material, 1.0% by weight of styrene-butadiene rubber as a binder, 1.0% by weight of carboxymethylcellulose as a thickener, and an appropriate amount of deionized water as a viscosity adjusting solvent.
[0078] The obtained negative electrode active material slurry was applied to both sides of a 10 μm thick copper foil, which served as the negative electrode current collector, and dried to form a negative electrode composite layer. The amount of negative electrode composite layer applied to each side was 70 g / m². 2 Next, the positive electrode was pressed to achieve a density of 1.45 g / cm³ in the negative electrode composite layer. 3 Then, the negative electrode composite layer was cut so that the uncoated portion protruded in a rectangular shape from one side of the rectangle where the negative electrode composite layer was coated, forming the negative electrode current collector lead.
[0079] <Fabrication of electrode elements> Next, electrode elements were fabricated by alternately stacking positive and negative electrodes with a separator connected in a zigzag pattern. The separator used was a 12 μm thick polyolefin substrate fabricated by wet stretching, with alumina particles coated on both sides to a thickness of 2 μm per side. The A / B value of the separator used was 2.2, where A is the greater tensile strength and B is the lesser tensile strength in the TD and MD directions. Subsequently, the positive electrode current collector lead and the negative electrode current collector lead were bundled together and connected to the positive electrode current collector tab and the negative electrode current collector tab by ultrasonic welding to fabricate the electrode elements.
[0080] <Preparation of non-aqueous electrolyte> The electrolyte used was a mixed solvent of ethylene carbonate, ethyl methyl carbonate, and dimethyl carbonate in a volume ratio of 2:5:3, to which LiPF6 was dissolved at a concentration of 1.3 mol / L as a lithium salt, and vinylidene carbonate was added at a concentration of 0.5% by weight.
[0081] <Fabrication of non-aqueous electrolyte secondary batteries> Two rectangular laminate films were prepared as the outer casing, each having a structure in which a heat-sealable resin layer made of polyolefin, a metal layer made of aluminum foil, and a protective layer made of nylon resin and polyester resin are laminated in that order. A recess was formed in one of the laminate films, and the heat-sealable resin layers of the two laminate films were placed facing each other, and the laminate films were superimposed mirror-image so that the electrode elements were housed in the recess. The electrode elements were positioned so that the portion of each terminal (tab) where the heat-sealable resin part is formed passes between the periphery of the two laminate films, and a portion of each terminal is exposed to the outside. In this state, the heat-sealable resin layers of the periphery of the laminate films were heat-sealed together on three sides, including the side from which each terminal extends. Subsequently, the non-aqueous electrolyte prepared above was injected through the one side of the outer casing that was not heat-sealed. Next, under reduced pressure, the remaining side of the outer casing was heat-fused to create a non-aqueous electrolyte secondary battery.
[0082] <Rate Characteristics Test> The fabricated batteries were subjected to charge-discharge tests in a constant temperature chamber at 25°C. After initial charging and activation, the batteries underwent discharge rate characteristic testing. For the initial charge, one cycle was performed consisting of constant current / constant voltage charging with a current of 0.1 ItA, a voltage of 4.2 V, and a cutoff current of 0.05 ItA, followed by a constant current discharge of 0.1 ItA and a cutoff voltage of 2.7 V. For activation, four cycles were performed consisting of constant current / constant voltage charging with a current of 0.2 ItA, a voltage of 4.2 V, and a cutoff current of 0.05 ItA, followed by a constant current discharge of 0.2 ItA and a cutoff voltage of 2.7 V. For the discharge rate characteristic test, charging was performed using constant current and constant voltage charging with a current of 0.5 ItA, a voltage of 4.2 V, and a cutoff current of 0.05 C. Discharging was performed using constant current discharge with current values of 0.2 ItA and 2.0 ItA, and a cutoff voltage of 2.7 V. A 15-minute rest period was set after each test, both after charging and after discharging.
[0083] <Nail-piercing test> The fabricated non-aqueous electrolyte secondary battery (cell) was pre-charged with constant current-constant voltage (cutoff current: 0.05C) at an upper voltage limit of 4.2V and a current of 0.5C. A nail (made of iron, 5mm in diameter) was driven into the center of the cell at a nail-driving speed of 10mm / second until it penetrated completely. The maximum surface temperature of the cell after nail penetration (hereinafter referred to as "surface temperature") was measured. In addition, the appearance of the cell was checked one hour after nail penetration to confirm whether there was any cracking outside the nail-driving area.
[0084] <Overall Rating> An overall evaluation was conducted based on the discharge rate characteristics and the results of the nail penetration test. As shown in Table 1 below, the overall evaluation was rated as follows, from best to worst, based on the combination of results from each test: ◎, ○, △, ×. [Table 1]
[0085] Table 2 shows the battery configuration and test results in Example 1. [Table 2]
[0086] (Example 2) In Example 2, the same configuration and experimental method as in Example 1 were used, except that the amount of carbon nanotubes added to the positive electrode was 0.5% by weight. The configuration of the battery in Example 2 and the test results are shown in Table 2.
[0087] (Example 3) In Example 3, the same configuration and experimental method as in Example 1 were used, except that the amount of carbon nanotubes added to the positive electrode was 0.8% by weight. The configuration of the battery in Example 3 and the test results are shown in Table 2.
[0088] (Example 4) In Example 4, the same configuration and experimental method as in Example 1 were used, except that the amount of carbon nanotubes added to the positive electrode was 0.9% by weight. The configuration of the battery in Example 4 and the test results are shown in Table 2.
[0089] (Example 5) In Example 5, the same configuration and experimental method as in Example 1 were used, except that the first positive electrode active material was LiCoO2 (LCO). The configuration of the battery in Example 5 and the test results are shown in Table 2.
[0090] (Example 6) In Example 6, the same configuration and experimental method as in Example 1 were used, except that the A / B value of the separator was 1.1. The battery configuration and test results in Example 6 are shown in Table 2.
[0091] (Example 7) In Example 7, the same configuration and experimental method as in Example 1 were used, except that the A / B value of the separator was 4.9. The battery configuration and test results in Example 7 are shown in Table 2.
[0092] (Example 8) In Example 8, the same configuration and experimental method as in Example 1 were used, except that the diameter of the carbon nanotubes was 4 nm. The configuration of the battery in Example 8 and the test results are shown in Table 2.
[0093] (Example 9) In Example 9, the same configuration and experimental method as in Example 1 were used, except that the diameter of the carbon nanotubes was 5 nm. The configuration of the battery in Example 9 and the test results are shown in Table 2.
[0094] (Example 10) In Example 10, the same configuration and experimental method as in Example 1 were used, except that the diameter of the carbon nanotubes was 6 nm. The configuration of the battery in Example 10 and the test results are shown in Table 2.
[0095] (Example 11) In Example 11, the same configuration and experimental method as in Example 1 were used, except that the diameter of the carbon nanotubes was 10 nm. The configuration of the battery in Example 11 and the test results are shown in Table 2.
[0096] (Example 12) In Example 12, the same configuration and experimental method as in Example 1 were used, except that the inorganic material was boehmite. The configuration of the battery in Example 12 and the test results are shown in Table 2.
[0097] (Example 13) In Example 13, the same configuration and experimental method as in Example 1 were used, except that the inorganic material was barium sulfate. The configuration of the battery in Example 13 and the test results are shown in Table 2.
[0098] (Example 14) In Example 14, the same configuration and experimental method as in Example 1 were used, except that the thickness of one side of the coating layer was 3 μm and the total thickness was 6 μm. The configuration of the battery in Example 14 and the test results are shown in Table 2.
[0099] (Example 15) In Example 15, the same configuration and experimental method as in Example 1 were used, except that the thickness of one side of the coating layer was 1 μm and the total thickness was 2 μm. The configuration of the battery in Example 15 and the test results are shown in Table 2.
[0100] (Comparative Example 1) Comparative Example 1 used the same configuration and experimental method as Example 1, except that the amount of carbon nanotubes added to the positive electrode was 0.4% by weight. The configuration of the battery and the test results in Comparative Example 1 are shown in Table 2.
[0101] (Comparative Example 2) In Comparative Example 2, the same configuration and experimental method as in Example 1 were used, except that the amount of carbon nanotubes added to the positive electrode was 1.0% by weight. The configuration of the battery in Comparative Example 2 and the test results are shown in Table 2.
[0102] (Comparative Example 3) In Comparative Example 3, carbon black and graphite were used as conductive additives for the positive electrode, with the only difference being that the amount of carbon black added was 3.0% by weight and the amount of graphite added was 2.0% by weight. The configuration and experimental method were the same as in Example 1. The configuration of the battery in Comparative Example 3 and the test results are shown in Table 2.
[0103] (Comparative Example 4) In Comparative Example 4, carbon black and graphite were used as conductive additives for the positive electrode, with the only difference being that the amount of carbon black added was 0.4% by weight and the amount of graphite added was 0.3% by weight. The configuration and experimental method were the same as in Example 1. The configuration of the battery in Comparative Example 4 and the test results are shown in Table 2.
[0104] (Comparative Example 5) Comparative Example 5 used the same configuration and experimental method as Example 1, except that a separator without a coating layer was used. The battery configuration and test results for Comparative Example 5 are shown in Table 2.
[0105] (Comparative Example 6) Comparative Example 6 used the same configuration and experimental method as Example 1, except that the A / B value of the separator was 9.9. The battery configuration and test results for Comparative Example 6 are shown in Table 2.
[0106] (Comparative Example 7) Comparative Example 7 used the same configuration and experimental method as Comparative Example 3, except that lithium cobalt oxide (LCO) was used as the first positive electrode active material. The battery configuration and test results for Comparative Example 7 are shown in Table 2.
[0107] Table 2 shows the electrode parameters, electrochemical characteristics, and nail-piercing test results for each of the examples and comparative examples. Examples 1-3, 5-10, and 12-15 did not ignite or emit smoke when pierced with a nail, and the discharge rate characteristics showed high values exceeding 90%. On the other hand, in Comparative Example 1, where 0.4% by weight of carbon nanotubes was added to the conductive agent, the discharge rate characteristic was less than 90%. This is presumed to be because the amount of conductive agent added was insufficient, preventing the formation of adequate conductive paths in the electrode. In Comparative Example 2, which used 1.0 wt% carbon nanotubes as the conductive agent, and in Comparative Examples 3, 4, and 7, which used carbon black and graphite as conductive agents and a double-sided coated separator with alumina, ignition was observed when a nail was driven into the material. This is presumed to be because, when the nail came into contact with the positive electrode, the conductive agent aggregated at certain points and the nail came into contact with the electrode, causing a large current to flow locally. In Comparative Example 5, which used a separator without a coating layer, and in Comparative Example 6, where the A / B ratio exceeded 5, ignition was observed when a nail was driven into the material. This is thought to be because the separator was unable to prevent the expansion of the short circuit when the nail was driven into the material.
[0108] The lithium-ion secondary battery of the present invention can be applied to a variety of applications requiring rapid charging and discharging, such as power tools, drones, robots, electric motorcycles, and many other applications. [Explanation of Symbols]
[0109] 1. Lithium-ion rechargeable battery 2. Exterior 3 electrode groups 4 Positive electrode 5 Negative electrode 6 Separators 7 Positive terminal 8 Negative terminal 41. Positive electrode composite layer 42 Positive electrode current collector 51 Negative electrode layer 52 Negative electrode current collector
Claims
1. Equipped with a positive electrode, a negative electrode, and a separator, The positive electrode is composed of a positive electrode composite layer comprising a positive electrode active material, a conductive additive, and a binder, and a current collector foil. The positive electrode active material includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material is a layered compound represented by the general formula shown in equation (1) below, The second positive electrode active material is a phosphate compound having an olivine structure represented by the general formula shown in equation (2) below. The conductive additive contains carbon nanotubes in a proportion greater than 0.4% by weight and less than 1.0% by weight relative to the total weight of the positive electrode composite layer. The separator has a coating layer made of an inorganic material on at least one surface of the sheet that serves as the substrate for the separator. When the greater of the tensile strengths of the substrate in the TD direction and MD direction is denoted as A, and the smaller of the tensile strengths is denoted as B, the value of A / B is 1.0 or more and 5.0 or less. A lithium-ion secondary battery characterized by the following features. Li a Ni x Co y M1 1-x-y O 2 (However, 0 < a ≤ 1.2, 0 ≤ x ≤ 0.9, 0 < y ≤ 1, 0 < x + y ≤ 1) ... (1) LiMn z M2 b Fe 1-z-b PO 4 (where 0<z≤0.9, 0≤b≤0.1, 0<z+b<1) ... (2) M1 is commonly one or more elements selected from Na, Mg, Sc, Y, Mn, Fe, Cu, Zn, Al, Ti, Cr, Pb, Sb, and B. M2 is commonly one or more elements selected from Na, Mg, Sc, Y, Co, Ni, Cu, Zn, Al, Ti, Cr, Pb, Sb, and B.
2. The inorganic material is one of alumina, barium sulfate, or boehmite. The lithium-ion secondary battery according to feature 1.
3. The total thickness of the coating layer is 2 μm or more. The lithium-ion secondary battery according to feature 1.
4. The coating layer is coated on both sides of the substrate. The lithium-ion secondary battery according to feature 1.
5. The average fiber diameter of the carbon nanotubes is between 4 nm and 10 nm. The lithium-ion secondary battery according to feature 1.
Citation Information
Patent Citations
Lithium-ion secondary battery separator and lithium-ion secondary battery
JP2020064879A